Microbiological study in coastal water of Port Dickson, Malaysia - Ainon Hamzah,; Saiful Hazwa Kipli,; Siti Rahil Ismail,; Rawlins Una,; Sukiman Sarmani, (Universiti Kebangsaan Malaysia, 2011)
The microbial composition in coastal water of the Port Dickson beach in Negeri Sembilan, Malaysia was analyzed using several microbial indicators for the purpose of selecting the best indicator for marine water pollution. The indicators studied were total coliform (TC), fecal coliform (FC), fecal streptococci (FS) and coliphage. Five locations were selected along the Port Dickson beaches and samplings were carried out in 1998 and 2001. The results showed an increase in the number of total coliform (TC), fecal coliform (FC) and fecal streptococci (FS) between these two sampling by 98.12%, 86.12% and 99%, respectively. The numbers of TC, FC and FS exceeded the recommended limit for recreational seawater based on U.S. EPA 1986 standard. There was a positive correlation between TC, FC and FS and negative to coliphages.